IMPLEMENTASI MANAJEMEN MUTU DALAM PENDIDIKAN ISLAM - RAHMAT KURNIAWAN; ANDIKA ASMARA; ALMA MUTIA; NUR INSANI; RATNA 1; KAMUS 1 (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2024)
This article aims to explain how the implementation of quality management in Islamic education in Indonesia. The method used is a qualitative research method (library research) using literature (literature), both in the form of books, e-books, journals, and reports on previous research findings. The research findings show that issues related to quality are still a major concern in educational institutions, especially in Islamic education. The results illustrate that attention to these aspects can make a positive contribution to the progress of Islamic education in Indonesia. As for the conclusion of this article, to improve the quality of education, it is necessary to pay attention to four factors, namely input quality, process quality, output, and outcame.